2021
DOI: 10.1148/radiol.2021202363
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning–based Differentiation of Benign and Premalignant Colorectal Polyps Detected with CT Colonography in an Asymptomatic Screening Population: A Proof-of-Concept Study

Abstract: Background: CT colonography does not enable definite differentiation between benign and premalignant colorectal polyps.Purpose: To perform machine learning-based differentiation of benign and premalignant colorectal polyps detected with CT colonography in an average-risk asymptomatic colorectal cancer screening sample with external validation using radiomics. Materials and Methods:In this secondary analysis of a prospective trial, colorectal polyps of all size categories and morphologies were manually segmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The results of this research revealed that the area under the receiver operating characteristic (ROC) curve (AUC) of classification in distinguishing colorectal lesions (neoplastic and non-neoplastic) was improved from 0.74 (by using the image intensity solely) to 0.85 (by also using the texture features from high-order differentiations). In another study, Grosu et al [52] developed a machine learning method to distinguish between benign and precancerous CTC-detected colorectal polyps in an average-risk asymptomatic CRC screening sample. The current classification algorithm showed promising results with a sensitivity of 82%, a specificity of 85%, and an AUC of 0.91.…”
Section: Virtual Colonoscopymentioning
confidence: 99%
“…The results of this research revealed that the area under the receiver operating characteristic (ROC) curve (AUC) of classification in distinguishing colorectal lesions (neoplastic and non-neoplastic) was improved from 0.74 (by using the image intensity solely) to 0.85 (by also using the texture features from high-order differentiations). In another study, Grosu et al [52] developed a machine learning method to distinguish between benign and precancerous CTC-detected colorectal polyps in an average-risk asymptomatic CRC screening sample. The current classification algorithm showed promising results with a sensitivity of 82%, a specificity of 85%, and an AUC of 0.91.…”
Section: Virtual Colonoscopymentioning
confidence: 99%
“…The entire code we used during the model establishment is publicly available on the development platform Github ( ) ( 25 ). After 142 lesions were divided into LGG or GBM based on histopathological examination, Random Forest classifier was used to construct a radiomics model.…”
Section: Methodsmentioning
confidence: 99%
“…Histopathological polyp class was blinded for all readers. Colorectal polyps were manually segmented in multiplanar 2D CT colonography images by a board-certified radiologist (8 years of experience in CT colonography imaging; completed a specialised hands-on workshop on CT colonography) and two radiology residents (3 years of experience in CT colonography imaging; one completed a specialised hands-on workshop on CT colonography) in equal amounts, as described in detail beforehand [16]. For exact retrospective polyp re-detection, 2D and virtual fly-through 3D CT colonography reconstructions were used (Fig.…”
Section: Polyp Segmentationmentioning
confidence: 99%
“…First studies have shown that machine learning-based CT colonography using radiomics may allow non-invasive differentiation of benign and premalignant colorectal polyps [15,16]. These radiomics approaches consist of three steps.…”
Section: Introductionmentioning
confidence: 99%